2001
DOI: 10.1603/0022-0493-94.3.686
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Insecticide Baits for Cockroach Control (Dictyoptera: Blattellidae) - Laboratory and Field Studies

Abstract: Several insecticide bait formulations were evaluated for their attractiveness to cockroaches in olfactometer assays in the laboratory and in trapping experiments in the field. Included in the assays were bait stations, gels, pastes, and a powder that contained one of the following active ingredients: abamectin, boric acid, chlorpyrifos, or hydramethylnon. There were significant differences among the baits in their attractiveness to the German cockroach, Blattella germanica (L.). In trapping experiments, Avert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(35 reference statements)
0
14
0
1
Order By: Relevance
“…Bait efficacy is influenced by many factors, including its attractiveness and palatability, 45,46 the toxicity of different active ingredients, 14,15,45 the presence and frequency of resistance alleles within the target insect population, 44,58 -63 its ability to affect secondary mortality 12 -14 and practical considerations such as bait distribution. 64 Here we demonstrate that bait performance could also be affected by a predictable interaction between the nutritional condition of the German cockroach, which is a consequence of its nutritional history, and bait macronutrient composition.…”
Section: Discussionmentioning
confidence: 99%
“…Bait efficacy is influenced by many factors, including its attractiveness and palatability, 45,46 the toxicity of different active ingredients, 14,15,45 the presence and frequency of resistance alleles within the target insect population, 44,58 -63 its ability to affect secondary mortality 12 -14 and practical considerations such as bait distribution. 64 Here we demonstrate that bait performance could also be affected by a predictable interaction between the nutritional condition of the German cockroach, which is a consequence of its nutritional history, and bait macronutrient composition.…”
Section: Discussionmentioning
confidence: 99%
“…Cockroaches were attracted to all gel baits investigated in the present study, although they were more attracted to the bait containing indoxacarb than to baits containing clothianidin and those containing 0.05% or 0.01% fipronil. Previous studies have also reported significant differences in gel bait attractiveness for German cockroaches (Durier & Rivault 2000;Nalyanya et al 2001). In the present study, mortality of German cockroaches was observed 2 h after eating gel baits, and the mortality rate increased throughout the 40-h 0.0001 0.0001 0.0001 0.0001 0.0001 0.0001 †Based on positive ranks.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have also reported significant differences in gel bait attractiveness for German cockroaches (Durier & Rivault ; Nalyanya et al . ). In the present study, mortality of German cockroaches was observed 2 h after eating gel baits, and the mortality rate increased throughout the 40‐h period after feeding (end of the test).…”
Section: Discussionmentioning
confidence: 96%
“…for growing and mating, determine their food preference. 5,11 While wandering for food, especially in a dirty place, its body might have contact with many typr of infectious agents. [21][22][23] These enviroment-derived microorganisms have diverse sensitivity/susceptibility patterns to antibiotics or antimicrobes, some of them are resistant strain.…”
mentioning
confidence: 99%
“…any places related or connected with waste water such as waste water pipe, cesspits, septic tanks, sewers, rubbish dumps, refuse tips, dustbins and cupboards, drawers, underneath chairs, tables, water-sinks, water-baths and beds, behind refrigerators, cooking stoves, among (dirty) stacked dishes and even in almost any dark place available. [1][2][3][4][5][6] all of these related to their nitrogen metabolism, and their needs of this macro-nutrient(nitrogen) and other type of micro-nutrient and other electrolyte can be fulfilled thru waste water. 17 The association of cockroaches with various enteric pathogens, especially food-borne parasite, e.g protozoan and helminths, and also with bacterial pathogens have been extensively reported, but their prevalence varied, depend on the location.…”
mentioning
confidence: 99%